Synonymy: A Translation Procedure to Overcome Problems of SL and TL Cultural Differences - Adventina Putranti (Universitas Sanata Dharma, 2015)
Translation is reproducing equivalent message from a source language (SL) text into a target language (TL) text. This concept implies translators efforts to maintain message equivalence. On the other hand, the efforts may be hindered by cultural differences. In other words, cultural differences may cause problems in maintaining message equivalence in translation. A common problem found in translation is loss and gain of meaning. To overcome translation problems related to loss and gain of meaning as a result cultural differences, various translation procedures could be applied. Synonymy is one of many translation procedures commonly used. This procedure is applied when a translation is not the first literal translation of the SL text. This procedure is usually chosen when translators could not find the one-to-one substitute in the TL.